The Impact of Gardening on Dietary Inflammation: Mixed-Effect Models and Propensity Score Analyses - Callie M. Ogland-Hand, BA; Timothy H. Ciesielski, ScD, MD, MPH; Wyatt P. Bensken, PhD; Kathryn I. Poppe, MPH, RDN; Thomas E. Love, PhD; Darcy A. Freedman, PhD, MPH (Elsevier, 2024)
Introduction: Gardening has been found to increase vegetable intake and reduce BMI; this suggests that it may improve diets by lowering inflammatory content. The goal of this study goal was to evaluate the effect of gardening on Dietary Inflammatory Index scores. Methods: Longitudinal data were collected annually between 2015 and 2018 from adults in low-income, urban neighborhoods of Cleveland and Columbus, Ohio. The authors measured the association between gardening and Dietary Inflammatory Index in the full data set using multivariable mixed-effect models with a random intercept for participant (Model 1; n=409). To further explore potential causation, the author used propensity score analyses in a subset of the data by building a 1-to-1 matched model (Model 2; n=339). Results: Of 409 adults, 30.3% were gardeners with Dietary Inflammatory Index scores ranging from −6.228 to +6.225. Participating in gardening was associated with lower Dietary Inflammatory Index scores in the mixed-effects model (−0.45; 95% CI= −0.85, −0.04; Model 1) and the 1-to-1 matched model (−0.77; 95% CI= −1.40, −0.14; Model 2). Conclusions: The analyses indicate that gardeners had lower Dietary Inflammatory Index scores than nongardeners, implying lower diet-driven inflammation. These findings highlight the potential for a causal relationship between gardening and Dietary Inflammatory Index, which should be confirmed in future studies. If this relationship is validated, strategies to increase gardening may be worth testing as primary prevention tools for diet-driven chronic disease.